A new revised Graded Naming Test and new normative data including older adults (80–97 years). Issue 3 (9th October 2019) - Murphy, Patrick; Chan, Edgar; Mo, Stella; Cipolotti, Lisa
Abstract : The Graded Naming Test (GNT) is commonly used in clinical and research settings to assess nominal functions. However, normative data for the GNT is over 20 years old and norms for the older adult population are rather limited. Hence, confounding factors such as generational familiarity due to cultural changes need to be considered when applying the currently available norms. Moreover, normative data for the older population (80–97) are virtually absent. Such factors can be powerful confounds that can lead to incorrect interpretation of test scores. We gathered data for the GNT from 326 healthy controls aged between 18 and 97 years. Surprisingly, we found no decline in performance for older adults, even for the cohort aged 80–97 years ( N = 40). In contrast, the youngest cohort (aged 18–29 years) performed unexpectedly below the whole sample mean. An item‐by‐item analysis revealed that five test items were unfamiliar to the youngest age cohort. To account for this generational familiarity effect, we created a revised 25‐item GNT. The performance of the youngest cohort on the 25‐item GNT was no longer below the whole sample mean. The performance of the oldest cohort (80–97 years old) on the revised GNT was characterized by a significant decline in performance for the oldest cohort with an average NART IQ. By contrast, those with a NART IQ above the average range did not show a decline. This suggests that factors such cognitive reserve arrested the decline in performance in the oldest age cohort with higher premorbid IQ.